2014
DOI: 10.1002/anie.201400835
|View full text |Cite
|
Sign up to set email alerts
|

Guest‐Induced Photophysical Property Switching of Artificial Light‐Harvesting Dendrimers

Abstract: An artificial light-harvesting multiporphyrin dendrimer (8P(Zn)P(FB)) composed of a focal freebase porphyrin (P(FB)) with eight zinc(II) porphyrin (P(Zn)) wings exhibited unique photophysical property switching in response to specific guest molecule binding. UV/Vis titration studies indicated stable 1:2 host-guest complex formation between 8P(Zn)P(FB) and meso-tetrakis(4-pyridyl)-porphyrin (TPyP) for which the first and second association constants were estimated to be >10(8) M(-1) and 3.0×10(7) M(-1), respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…[51] There have been several reports of dendritic structures that exhibit a Stokes' shift that is large enough to reduce reabsorption. [52][53][54][55][56] For example, Akkaya et al reported a dendritic system composed of borondipyrromethene (bodipy) dyes with varying degrees of functionalization with styryl groups.…”
Section: Tuning the Effective Stokes' Shift Using Energy Transfer Casmentioning
confidence: 99%
“…[51] There have been several reports of dendritic structures that exhibit a Stokes' shift that is large enough to reduce reabsorption. [52][53][54][55][56] For example, Akkaya et al reported a dendritic system composed of borondipyrromethene (bodipy) dyes with varying degrees of functionalization with styryl groups.…”
Section: Tuning the Effective Stokes' Shift Using Energy Transfer Casmentioning
confidence: 99%
“…Considering the characteristic spectral evolution shown in decay associated spectra and that the singlet excited state of zinc porphyrin species mainly decays via intersystem crossing to a triplet state rather than fluorescence emission, we can assign the TA decay of monomeric zinc porphyrin to intersystem crossing. [40][41][42][43][44] Unlike the spectral evolution of the monomeric zinc porphyrin, the TA spectra of dendrimers show distinct and fast spectral changes. The ground state bleach (GSB) of donor (543 nm) is reduced, while the GSB of acceptor (517 nm) is increased, and the SE of donor (637 nm) is shifted to longer wavelengths.…”
Section: Fret Efficiencies Of Multiporphyrin Dendrimersmentioning
confidence: 99%
“…These branches may contain a large number of reactive end groups. Several porphyrin-core dendrimers were synthesized and their properties investigated in recent years [20,21,22,23,24]. The biomedical applications of these compounds are also of interest [25].…”
Section: Introductionmentioning
confidence: 99%